LISA telescope: phase noise due to pointing jitter. (18th September 2019) - Vinet, Jean-Yves; Christensen, Nelson; Dinu-Jaeger, Nicoleta; Lintz, Michel; Man, Nary; Pichot, Mikhaël
Abstract: In a space based gravitational wave antenna like LISA, involving long light paths linking distant emitter/receiver spacecrafts, signal detection amounts to measuring the light-distance variations through a phase change at the receiver. This is why spurious phase fluctuations due to various mechanical/thermal effects must be carefully studied. We consider here a possible pointing jitter in the light beam sent from the emitter. We show how the resulting phase noise depends on the quality of the wavefront due to the incident beam impinging on the telescope and due to the imperfections of the telescope itself. Namely, we numerically assess the crossed influence of various defects (aberrations and astigmatisms), inherent to a real telescope with pointing fluctuations.